Annual acknowledgment of reviewers - Health Prospect, The (Health Prospect, 2016)
The Editorial Committee wishes to express gratitude to all the reviewers who contributed to Health Prospect in the year 2015. Without their contribution, sucessful publication of papers would not have been possible. They evaluated the manuscripts submitted to the journal, helped authors improve the paper, and us make a decision.